Assessment of Patients’ Perception of Mechanical Ventilation (Endotracheal Tube) and Intensive Care Unit Post Cardiac Surgery - Khalida Alwan Mansour 1 , Bassima Amir Naji 2 , Bushra Khairullah Khanjar3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Treatment and mechanical ventilation in the intensive care unit may get a variety of physicaland psychological discomfort for patients.Objectives: To assess the perception of patients about the intensive care unit (ICU) and stressful experiencesabout mechanical ventilation in ICU. And identify an association between patient perceptions withdemographic characteristics.Methodology: a descriptive study (cross-sectional study) for the purposive sample of 80 patients of postcardiac surgery (hospitalized) in Ibn Albetar and Iraqi Center of Heart Disease (Gaze AL-Hariri hospital).Data were analyzed to achieve the goal of the study have been a questionnaire prepared according to theliterature review, it is composed of 3 parts, first part demographic data and, the information related ICU, thesecond parts, stressful experiences of adult patients who received mechanical ventilation (Endotrachealtube) (ETT) at ICU, and third parts, patient perception related to the environment at ICU. The validity ofthe questionnaire through a number of experts in the college of the nursing university in Baghdad.Results: The study showed (47.5%) of the sample was within (50-59) years, 25% of them from primaryschool or less, (85%) of them the residence area was urban, the study showed that the high percentage(62.5%) of the cardiac surgery patient was the moderate level of stressful experience during mechanicalventilation (Endotracheal tube) (ETT) at intensive car unite (ICU) while only (10%) of patients with alow-level of stressful experiences. The results also showed the majority (90 %) of patients with a moderatelevel of the perception of patients of the intensive care unit.Conclusions: The majority of cardiac surgery patients where moderate levels of perception of mechanicalventilation (Endotracheal tube) (ETT) and of the ICU.